Isoliquiritigenin-Induced Differentiation in Mouse Melanoma B16F0 Cell Line. (10th December 2012) - Chen, Xiaoyu; Zhang, Bo; Yuan, Xuan; Yang, Fan; Liu, Jinglei; Zhao, Hong; Liu, Liangliang; Wang, Yanming; Wang, Zhenhua; Zheng, Qiusheng
Abstract : The chemotherapeutical treatment is very limited for malignant melanoma, a highly lethal disease occurs globally. Natural products derived from traditional Chinese medicine licorice are attractive in quest new treatments due to their anti-tumor activities. A new dietary flavonoid isoliquiritigenin (ISL) were thus investigated to indentify its anti-melanoma activities on mouse melanoma B16F0 cells in present study. Using biochemical and free radical biological experiments in vitro, we identified the pro-differentiated profiles of ISL and evaluated the role of reactive oxygen species (ROS) during B16F0 cell differentiation. The data showed a strong dose-response relationship between ISL exposure and the characteristics of B16F0 differentiation in terms of morphology changes and melanogenesis. The accumulated intercellular ROS during exposure are necessary to support ISL-induced differentiation, which was proven by additional redox modulators. It was confirmed further by the relative activities of enzymes and genes modulated melanogenesis in ISL-treatments with or without ROS modulators. The tumorigenicity of ISL-treated cells was limited significantly by using the colony formation assay in vitro and an animal model assay in vivo respectively. Our research demonstrated that isoliquiritigenin is a differentiation-inducing agent, and its mechanisms involve ROS accumulation facilitating melanogenesis.